Faithful to continuance [videorecording (VHS)] : [legacy of the Plateau people] (Mimbres Fever Productions, 2002)
The Plateau culture as revealed by six artists: Joe Feddersen, Elizabeth Woody, Lillian Pitt, Elaine Timentwa Emerson, Pat Courtney Gold, and Maynard White Owl Lavadour.